Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Southwest)--Coho Salmon - Hassler, Thomas J. (Washington, D.C. U.S. Department of the Interior, 1987)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.70)
Keywords: Invertebrates; Fishes; History; Coho salmon--Pacific Southwest